2018
DOI: 10.18632/oncotarget.25772
|View full text |Cite
|
Sign up to set email alerts
|

HighO-linkedN-acetylglucosamine transferase expression predicts poor survival in patients with early stage lung adenocarcinoma

Abstract: Tumor cell heterogeneity can make selection of appropriate interventions to lung cancer a challenge. Novel biomarkers predictive of disease risk and treatment response are needed to improve personalized treatment strategies. O-GlcNAcylation, the attachment of β-N-acetylglucosamine (O-GlcNAc) to serine or threonine residues of intracellular proteins, modulates protein functions and is implicated in cancer pathogenesis. O-GlcNAc-transferase (OGT) and O-GlcNAcase (OGA) catalyze O-GlcNAc addition and removal, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 25 publications
1
26
2
Order By: Relevance
“…With the sparse information, it is unclear whether all cell types utilize conserved mechanisms to regulate the expression of OGA and OGT upon changes of cellular O -GlcNAcylation. We have previously revealed a positive correlation between OGT and OGA protein expression in lung adenocarcinoma tissues [ 20 ]. In this study, we further investigated the regulatory loops involved in adjusting the expression of the two O -GlcNAc-cycling enzymes when changes of cellular O -GlcNAcylation status occur in lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…With the sparse information, it is unclear whether all cell types utilize conserved mechanisms to regulate the expression of OGA and OGT upon changes of cellular O -GlcNAcylation. We have previously revealed a positive correlation between OGT and OGA protein expression in lung adenocarcinoma tissues [ 20 ]. In this study, we further investigated the regulatory loops involved in adjusting the expression of the two O -GlcNAc-cycling enzymes when changes of cellular O -GlcNAcylation status occur in lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Recently, several cancer studies have reported that elevated O-GlcNAc is associated with tumorigenesis and cancer cell metastasis. 12,[16][17][18][19][20][21][22][23][24][25] Moreover, several previous studies have shown that hyper-O-GlcNAc and overexpression of OGT were associated with worse clinicopathological outcomes in various cancers. 17,21,26,27 Osteosarcoma is most commonly found in children, adolescents and young adults, accounting for approximately 20% of all primary bone tumors.…”
mentioning
confidence: 99%
“…In many types of cancer such as breast, prostate, lung, colorectal, and esophageal cancers, higher levels of OGT/O-GlcNAcylation are observed (29), suggesting that alterations of the intracellular level of OGT and O-GlcNAcylation are tightly associated with tumorigenesis, which might further participate directly or indirectly in the regulation of the biological processes associated with cancer metastasis. For example, the increased levels of OGT/O-GlcNAcylation in patients with lung cancer or colon cancer are closely correlated with poor overall survival, as well as the anchorage-independent growth, migration, and invasion ability of lung and colon cancer cell lines (22,23,30,31). Elevated OGT proteins, as well as O-GlcNAcylation level, are also found in both breast cancer cells and tumor tissues (24,25).…”
Section: Imbalanced O-glcnacylation In Cancer Cellsmentioning
confidence: 99%